2021
DOI: 10.1212/nxi.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angiitis of the CNS

Abstract: Background and ObjectivesTo facilitate and improve the diagnostic and therapeutic process by systematically reviewing studies on patients with primary angiitis of the CNS (PACNS).MethodsWe searched PubMed, looking at the period between 1988 and February 2020. Studies with adult patients with PACNS were included. We extracted and pooled proportions using fixed-effects models. Main outcomes were proportions of patients with certain clinical, imaging, and laboratory characteristics and neurologic outcomes.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…We identified four reviews [15][16][17][18] pertinent to this Guideline; these differed in their precise focus and none aligned with our inclusion criteria so, although we considered these manuscripts, we did not incorporate their synthesis of results.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified four reviews [15][16][17][18] pertinent to this Guideline; these differed in their precise focus and none aligned with our inclusion criteria so, although we considered these manuscripts, we did not incorporate their synthesis of results.…”
Section: Literature Searchmentioning
confidence: 99%
“…3 Abnormal test results were reported in 74.4% and 75% of patients, respectively. In addition, the systematic review and meta-analysis by Beuker et al 17 reported CSF data on 581/911 patients with abnormalities reported in 75% samples.…”
Section: Diagnosismentioning
confidence: 99%
“…Increasing evidence suggests that angiogram-confirmed PACNS typically involves medium to large vessels, while biopsy-confirmed cases relate to small-vessel vasculitis [8]. Additional clinical and laboratory differences supporting this concept are summarized in Figure 3 [1].…”
Section: Discussionmentioning
confidence: 96%
“…CSF analysis in PACNS may be normal [45] or show pleocytosis and elevated protein [46]. Vascular imaging, including CT, MRI, or catheter angiography, may show vasospasm [48]. Brain biopsy remains the diagnostic gold standard [48].…”
Section: Vasculitismentioning
confidence: 99%
“…Vascular imaging, including CT, MRI, or catheter angiography, may show vasospasm [48]. Brain biopsy remains the diagnostic gold standard [48]. A study examining the incidence of MRI changes among 135 patients with NSCLC receiving ICI therapy found 11 patients with lesions suggestive of ischemic stroke and 4 with lesions suggestive of CNS vasculitis or encephalitis, though other clinical and paraclinical parameters were not reported [49].…”
Section: Vasculitismentioning
confidence: 99%